2009
DOI: 10.1002/anie.200806268
|View full text |Cite
|
Sign up to set email alerts
|

Interaction and Reaction of the Phenyl Radical with Water: A Source of OH Radicals

Abstract: That's radical! A photochemical reaction between the phenyl radical and water results in the abstraction of a hydrogen atom from water and the formation of a hydroxyl radical. The hydroxyl radical forms an OHpi hydrogen bond with benzene (see picture) and does not react with benzene thermally under the conditions of matrix isolation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 22 publications
1
49
0
Order By: Relevance
“… Experimental bond enthalpies of 113 and 119 for C 6 H 6 and HOH 24, 28, 47, respectively, corrected by zero‐point vibrational energies to estimate electronic contributions. …”
Section: Resultsmentioning
confidence: 99%
“… Experimental bond enthalpies of 113 and 119 for C 6 H 6 and HOH 24, 28, 47, respectively, corrected by zero‐point vibrational energies to estimate electronic contributions. …”
Section: Resultsmentioning
confidence: 99%
“…It seems therefore, that the hydration of the 5-U-yl•, described in the current communication, is a rare example of spontaneous H-atom transfer from water to a carbon centered radical. Owing to the unusual nature of our prediction we have checked the energetics of the reaction with the thermodynamically reliable G3B3 level 23 of calculations in which each of the reacting species in the hydrogen abstraction reaction [1-metyluracil-5-yl• + H 2 O → OH•+ 1-methyluracil] were treated separately and found ΔG = −0.2 kcal/mol in the gas phase and ΔG = 1.3 kcal/mol in water (PCM) for the overall reaction free energy change. This shows that the C5-H bond energy is comparable to the OH bond in water and strongly supports our DFT results.…”
Section: Discussionmentioning
confidence: 99%
“…Reactions of OH· and benzene were examined in 2009 [28] from both experimental and computational perspectives, and more recently with the most accurate calculations to date [29]. The reactions of naphthyl radical with acetylene were studied and it was shown that calculations could reach agreement with experiment [30].…”
Section: Introductionmentioning
confidence: 99%